2017
DOI: 10.1111/1751-7915.12799
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Lactobacillus rhamnosus GG and Candida and the involvement of exopolysaccharides

Abstract: SummaryA number of clinical studies have shown protective effects of lactobacilli against Candida species in the gastrointestinal tract, the urogenital tract and the oral cavity, while others did not show clear effects. Evidence on the mode of action of lactobacilli against Candida is also still lacking. In this study, the anti‐Candida activity of the model probiotic strain Lactobacillus rhamnosus GG was explored in different assays to determine molecular interactions. We found that L. rhamnosus GG was able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 56 publications
4
77
0
1
Order By: Relevance
“…Lactic acid in combination with low pH was shown to inhibit C. albicans [105]. No inhibition of C. albicans [14,17,106] or C. glabrata [14,17,107] was observed at a lactic acid concentration reached with the supernatant of a cultured L. rhamnosus strain. The capability and rate of production of lactic acid is Lactobacillus strain specific.…”
Section: Lactic Acidmentioning
confidence: 95%
See 1 more Smart Citation
“…Lactic acid in combination with low pH was shown to inhibit C. albicans [105]. No inhibition of C. albicans [14,17,106] or C. glabrata [14,17,107] was observed at a lactic acid concentration reached with the supernatant of a cultured L. rhamnosus strain. The capability and rate of production of lactic acid is Lactobacillus strain specific.…”
Section: Lactic Acidmentioning
confidence: 95%
“…Probiotics are defined by the WHO as live microorganisms that, when administered or consumed in adequate quantities, confer health benefits [4]. Applying Lactobacillus to treat fungal infections is based on the premise that certain Lactobacillus species exert a protective effect in vivo by reducing the adhesion of the fungus to the vaginal mucosa [11,12], production of organic acids [11,13,14] and favorable metabolites [15][16][17][18] as well as enhancing vaginal epithelial cell immune defense mechanisms [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, exopolysaccharides obtained from 10 8 CFU/mL of L. rhamnosus GG inhibited growth of C. albicans over 24 hours. Lower initial concentra-tion of lactobacteria (10 7 CFU) was observed to be insufficient for producing metabolites with anti-fungicidal activity (Allonsius et al, 2017). It should be mentioned that initial concentration of cells of probiotic strains, from which the authors obtained metabolites with high antifungicidal properties, corresponded to the amount of the primary producer used in our experiment.…”
Section: Discussionmentioning
confidence: 77%
“…In a previous study [12], we demonstrated that a preventive administration of Lcr35 ® strain had two in vitro effects: inhibition of C. albicans growth and biofilm formation on a Caco-2 cells monolayer. Anti-C. albicans properties targeting in particular the adhesion of the pathogen to the epithelial cells have been attributed to exopolysaccharides (EPS) by various studies [26,27]. We then hypothesized that Lcr35 ® may synthesize antimicrobial molecules including EPS.…”
Section: Discussionmentioning
confidence: 99%